The effects of sleep on prospective memory: A systematic review and meta-analysis. (October 2019) - Leong, Ruth L.F.; Cheng, Grand H.-L.; Chee, Michael W.L.; Lo, June C.
Summary: Prospective memory (PM) enables us to execute previously conceived intentions at a later time and is used when remembering to call a friend or submitting a proposal on time. Evidence that sleep benefits PM is presently mixed. Further, when a benefit is observed, it is unclear if this is achieved through improvements in strategic monitoring (maintaining an intention in mind and searching for cues) or spontaneous retrieval (an automatic process occurring without preparatory attention). We conducted a meta-analysis of 24 independent samples (N = 165, 432) to quantify the effect of sleep on PM and gain clarity regarding the retrieval process benefitted by sleep. Cohen's d with 95% confidence intervals (CI95 ) were derived using random-effects models. The benefit of sleep on PM was statistically significant and in the small to medium range ( d  = 0.41, CI95  = 0.25–0.56). Moreover, sleep did not appear to influence monitoring ( d  = −0.11, CI95  = −0.40–0.17). In contrast, the benefits of sleep are significantly greater when the likelihood of spontaneous retrieval is high ( d  = 0.94, CI95  = 0.44–1.44) versus low ( d  = 0.45, CI95  = −0.02–0.93), suggesting that sleep may leverage on spontaneous retrieval processes to improve PM. These findings inform theoretical models of sleep and PM that could sharpen strategies to improve memory function in vulnerable populations.